Spectrofluorimetric determination of amlodipine in human plasma without derivatization - Yucel Kadioglu; Murat Ozturk (Universidade de São Paulo, 2012)
A rapid and sensitive spectrofluorimetric method was developed for the determination of amlodipine (AD), a calcium channel blocker, in the plasma. The type of solvent, the wavelength range, and the range of AD concentration were selected to optimize the experimental conditions. The calibration curves were linear (r² >0.997) in the concentration range of 0.1-12.5 ppm of AD. The limit of quantitation and limit of detection values for the method for plasma samples were 0.1 ppm and 0.07 ppm, respectively. The precision calculated as the relative standard deviation was less than 3.5%, and the accuracy (relative error) was better than 5.5% (n=6). The method developed in this study can be directly and easily applied for the determination of AD in the plasma without derivatization in plasma. Método espectrofluorometrico rápido e sensível é descrito para a determinação de anlodipina (AD), um bloqueador de canais de cálcio, em amostras de plasma. O tipo de solvente, a faixa de comprimento de onda e a faixa de concentração foram escolhidas a fim de otimizar as condições experimentais. As curvas de calibração foram lineares (r > 0,997) na faixa de concentração de 0,1-12,5 ppm de AD. Os valores LoQ e LoD do método para amostras de plasma foram 0,1 ppm e 0,07 ppm, respectivamente. A precisão calculada como desvio padrão relativo (RSD) foi menor do que 3,5% e a precisão (erro relativo) foi melhor do que 5,5% (n=6). O método desenvolvido neste estudo pode ser fácil e diretamente aplicado para a determinação de AD sem derivatização no plasma.